You are on page 1of 7

EECS 203: Discrete Mathematics

Fall 2019
Natural Deduction Practice Problems

1.
Using Natural Deduction, prove

(p → q) ∧ ¬(p ∧ q)
¬p

Solution:

 (p → q) ∧ ¬(p ∧ q) Premise
 p→q ∧ − elim 1
 ¬(p ∧ q) ∧ − elim 1
 p Assumption
 q → −elim 2, 4
 p∧q ∧ − intro 4, 5
 F ¬ − elim 6, 3
 ¬p ¬ − intro 4 − 7

1
2.
Using Natural Deduction, prove

(P (x) → Q(x)) ∧ (R(x) → S(x))


(P (x) ∨ R(x)) → (Q(x) ∨ S(x))

Solution:

 (P (x) → Q(x)) ∧ (R(x) → S(x)) Premise


 P (x) → Q(x) ∧ − elim 1
 R(x) → S(x) ∧ − elim 1
 P (x) ∨ R(x) Assumption
 P (x) Assumption
 Q(x) → −elim 2, 5
 Q(x) ∨ S(x) ∨ − intro 6
 R(x) Assumption
 S(x) → −elim 3, 8
 Q(x) ∨ S(x) ∨ − intro 9
 Q(x) ∨ S(x) ∨ − elim 4, 5 − 7, 8 − 10
 (P (x) ∨ R(x)) → (Q(x) ∨ S(x)) → −intro 4 − 11

2
3.
Using Natural Deduction, prove

(p ↔ q), (q → s), ¬s
¬p ∧ ¬q

Solution:

 p↔q Premise
 q→s Premise
 ¬s Premise
 q Assumption
 s → −elim 2, 4
 F ¬ − elim 3, 5
 ¬q ¬ − intro 4 − 6
 p Assumption
 q ↔ −elim 1, 8
 F ¬ − elim 7, 9
 ¬p ¬ − intro 8 − 10
 ¬p ∧ ¬q ∧ − intro 7, 11

*Note that once we have p ↔ q and ¬q, we cannot directly use a Natural Deduction
rule to conclude ¬p, but can conclude this using a negation introduction (see steps 8-10).

3
4.
Using ONLY Natural Deduction, prove
¬p → j, j → m
∴ m∨p

Solution:

 ¬p → j Premise
 j→m Premise
 ¬(m ∨ p) Assumption
 p Assumption
 m∨p ∨ − intro(4)
 F ¬ − elim(3, 5)
 ¬p ¬ − intro(4 − 6)
 j → −elim(1, 7)
 m → −elim(2, 8)
 m∨p ∨ − intro(9)
 F ¬ − elim(3, 10)
 ¬¬(m ∨ p) ¬ − intro(3 − 11)
 m∨p ¬ − elim(12)

4
5.
Using Natural Deduction, prove

∀x(P (x) → Q(x)) and ∀x¬Q(x)


∀x¬P (x)

Solution:

 ∀x(P (x) → Q(x)) Premise


 ∀x¬Q(x) Premise
 c
 P (c) → Q(c) ∀ − elim 1
 ¬Q(c) ∀ − elim 2
 P (c) assumption
 Q(c) → −elim 6, 4
 F ¬ − elim 7, 5
 ¬P (c) ¬ − intro 6 − 8
 ∀x¬P (x) ∀ − intro 3 − 9

5
6.
Using Natural Deduction, prove

∀x(P (x) → Q(x))


∀x((Q(x) → R(x)) → (P (x) → R(x))

Solution:

 ∀x(P (x) → Q(x)) Premise


 x0
 P (x0 ) → Q(x0 ) ∀ − elim 1
 Q(x0 ) → R(x0 ) Assumption
 P (x0 ) Assumption
 Q(x0 ) → −elim 3, 5
 R(x0 ) → −elim 4, 6
 P (x0 ) → R(x0 ) → −intro 5 − 7
 (Q(x0 ) → R(x0 )) → (P (x0 ) → R(x0 )) → −intro 4 − 8
 ∀x(Q(x0 ) → R(x0 )) → (P (x0 ) → R(x0 )) ∀ − intro 2 − 9

6
7.
Using ONLY Natural Deduction, prove

∀x∃y(P (x) → Q(y)), ∃xP (x)


∴ ∃yQ(y)

Solution:

 ∀x∃y(P (x) → Q(y)) Premise 1


 ∃xP (x) Premise 2
 a P (a) Assumption
 ∃yP (a) → Q(y) ∀ − elim(1)
 b P (a) → Q(b) Assumption
 Q(b) → −elim(3, 5)
 ∃yQ(y) ∃ − intro(6)
 ∃yQ(y) ∃ − elim(4, 5 − 7)
 ∃yQ(y) ∃ − elim(2, 3 − 8)

You might also like